2019
DOI: 10.1556/2051.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of needle characteristic on fibrous PEO produced by electrospinning

Abstract: The technique of electrospinning has been researched for several decades. Almost all parameters have been investigated in the past years, e.g., solution parameters, process parameters, and environmental conditions. Among the solution parameters, the viscosity of the polymer solution is an extremely important factor for fiber formation and morphology. In general, however, viscosity of the polymer solution is mostly controlled by the solution concentration or by the molecular weight of the polymer in electrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Moreover, this behavior consequently contributes to the electrospinning process. In a study by He et al, they investigated the shear strain effect by using different types of needles for electrospinning and concluded that the spinning solution’s shear rate was highly interconnected with the nanofiber production [ 42 ]. This can be related to the extent of polymer chain entanglements, due to the increased number of polymer molecules in the solutions, forming the stabile and continuous polymer jets [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this behavior consequently contributes to the electrospinning process. In a study by He et al, they investigated the shear strain effect by using different types of needles for electrospinning and concluded that the spinning solution’s shear rate was highly interconnected with the nanofiber production [ 42 ]. This can be related to the extent of polymer chain entanglements, due to the increased number of polymer molecules in the solutions, forming the stabile and continuous polymer jets [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the spinneret diameter affects the fiber diameter. In the research of He et al [ 75 ], it was found that the solution viscosity of the spinneret with a larger diameter increased at the end of the spinneret, which led to the increase in the fiber diameter. Therefore, the increase in the fiber diameter caused by the increase in the spinneret diameter was essentially due to the increase in the viscosity.…”
Section: Electrospinningmentioning
confidence: 99%
“…The diameter of the spinneret affects the diameter of the electrospun fiber, but the specific mechanism remains unclear. Until He et al [ 79 ] used spinnerets with different diameters to prepare PEO nanofibers for rheological experiments and the shear flow model to analyze the effect of spinneret diameter on PEO fibers’ diameter. The liquid viscosity on the tip of the spinneret with a larger diameter is higher; hence, the essence of spinneret diameter on fibers’ morphology is the effect of fluid viscosity on fibers.…”
Section: Electrospinningmentioning
confidence: 99%